Collective Action Dilemmas at Cultural Heritage Sites: An Application of the IAD-NAAS Framework. Issue 1 (17th September 2021) - Bertacchini, Enrico; Gould, Peter
Cultural heritage sites generate multiple streams of value to stakeholder groups whose interests and objectives frequently diverge. Contention over the conservation and appropriation of the values generated by heritage sites—whether economic returns, contributions to social or political cohesion, or sacred or other personal values associated with sites—leads to governance failures with adverse consequences both for the sites and for the various constituencies involved. This matter is gaining increasing attention among heritage scholars and practitioners. The conservation and management of cultural heritage sites can be conceived as a collective action problem arising from the strategic interaction of multiple actors. In this paper, we propose that the Institutional Analysis and Development (IAD) framework, in conjunction with McGinnis' Network of Adjacent Action Situations (NAAS), can be applied to diagnose the drivers of conflict and management failures at cultural heritage sites. By illuminating the inter-related governance dilemmas arising at two UNESCO cultural World Heritage sites, Machu Picchu in Peru and Angkor in Cambodia, our analysis reveals how either contention over governance dilemmas or the evolution of site management strategy can be better understood by using the IAD-NAAS frame to explore stakeholder dynamics within governance-related action situations that have interdependent outcomes.